In silico simulations of erythrocyte aquaporins with quantitative in vitro validation. Issue 36 (4th June 2020) - Chan, Ruth; Falato, Michael; Liang, Huiyun; Chen, Liao Y.
Abstract : Quantitatively predictive study of aquaporins in model erythrocyte membrane validated with cellular experiments. Abstract : Modelling water and membrane lipids is an essential element in the computational research of biophysical/biochemical processes such as water transport across the cell membrane. In this study, we examined the accuracies of two popular water models, TIP3P and TIP4P, in the molecular dynamics simulations of erythrocyte aquaporins (AQP1 and AQP3). We modelled the erythrocyte membrane as an asymmetric lipid bilayer with appropriate lipid compositions of its inner and outer leaflet, in comparison with a symmetric lipid bilayer of a single lipid type. We computed the AQP1/3 permeabilities with the transition state theory with full correction for recrossing events. We also conducted cell swelling assays for water transport across the erythrocyte membrane. The experimental results agree with the TIP3P water–erythrocyte membrane model, in confirmation of the expected accuracy of the erythrocyte membrane model, the TIP3P water model, and the CHARMM parameters for water–protein interactions.